Functional and preliminary characterisation of hydrocolloid from tamarillo (Solanum betaceum Cav.) puree - Gannasin, Sri Puvanesvari; Ramakrishnan, Yogeshini; Mohd Adzahan, Noranizan; Syed Muhammad, Sharifah Kharidah (MDPI, 2012)
Hydrocolloid from tamarillo (Solanum betaceum Cav.) puree was extracted using water and characterised for the first time. Proximate compositions of the extracted hydrocolloid were also determined. Functional characteristics such as water-holding capacity, oil-holding capacity, emulsifying activity, emulsion stability, foaming capacity and stability of the hydrocolloid were evaluated in comparison to that of commercial hydrocolloids. Its functional groups and degree of esterification were determined using Fourier Transform Infrared (FT-IR) spectroscopy. Monosaccharide profiling was done using reverse-phase high pressure liquid chromatography (RP-HPLC). Screening of various fruits for high hydrocolloid yield after water extraction resulted in tamarillo giving the highest yield. The yield on dry weight basis was 8.30%. The hydrocolloid constituted of 0.83% starch, 21.18% protein and 66.48% dietary fibre with 49.47% degree of esterification and the monosaccharides identified were mannose, ribose, rhamnose, galacturonic acid, glucose, galactose, xylose and arabinose. Higher oil-holding capacity, emulsifying activity and emulsion stability compared to commercial hydrocolloids propose its possible application as a food emulsifier and bile acid binder. Foaming capacity of 32.19% and good foam stabilisation (79.36% of initial foam volume after 2 h of foam formation) suggest its promising application in frothy beverages and other foam based food products. These findings suggest that water-extracted tamarillo hydrocolloid can be utilised as an alternative to low methoxyl pectin.